Critical Comments on the Sensorimotor Approach to Consciousness (Global Journal of Computer Science and Technology, 2014)
Cognitive neuroscience and contemporary physicalist philosophies of mind typically hold the view that minds somehow reduce to brain activity. This is achieved through representations that evolved to map reality and are subjected to computational activity. The received view has been criticized mostly through thought experiments that rely on the notion of qualia, but philosopher Alva NoEB; follows a different approach, called the 201C;sensorimotor theory201D;. Unlike the orthodoxy, NoEB; argues that our minds are not inside our bodies; they are better seen as a dynamic process of embodied cognition. This means mental activity emerges from our engagement with the world around us. NoEB;2019;s thesis is grounded on original arguments that are both empirical and philosophical in nature.
Keywords: neuroscience; representation; perception